Навчально-методична робота в Чернігівському педагогічному інституті (1954 – 1998 рр.) - Боровик, М. (Сiверянський лiтопис, 2015)
У статті мова йде про організацію процесу навчання та здійсненні внутрішнього
контролю в Чернігівському педагогічному інституті за час його існування. Зосереджено
увагу на трьох етапах формування та удосконалення системи навчально-методичної роботи вищого навчального закладу. В статье речь идёт об организации процесса обучения и осуществлении внутреннего контроля в Черниговском педагогическом институте за время его работы. Сосредоточено внимание на трёх этапах формирования и совершенствования системы
учебно-методической работы высшего учебного заведения. Well-organized teaching and guiding of lecturers of institute played an important role
in a preparation of qualified pedagogical staff. This problem wasn’t an object of historical
researches, so the article can fill this gap.
The article deals with three stages of the main changes in the management of teaching and
guiding in the institute. The first stage was from 1954 – 1955 to 1964 – 1965 years, when
only two faculties made learning activity. In the second phase – from the 1st of September,
1965 to 24th of August, 1991 there was increase of a number of faculties increased to six
and a system of teaching and guiding was formed. The third period covered the time from
the formation of the independent state Ukraine from the 24th of August, 1991 to reorganize
Pedagogical institute in Pedagogical University in the 13th of March, 1998.